Implementasi Pengembangan Karyawan Melalui Pendidikan dan Pelatihan Studi Kasus pada PT. Daeah E&C Indonesia - Efendi, Ramdhani; Arnu, Anggi Pasca (Peneliti.net, 2024)
Indonesia is a large country that has a large population. This data shows that the number of human resources in the work group is very high. Companies that have a workforce must be able to manage and develop the capabilities of their workforce well. This research discusses employee development methods through education and training. The research method uses qualitative methods. Based on the research results, it can be concluded that employee development by PT Daeah E&C Indonesia through education is carried out through training methods, coaching and counseling, and job rotation and planned progression, through training carried out through on the job training, outsider training and specialist courses. Employee development is carried out to increase employee abilities and knowledge in carrying out their duties so as to increase company productivity.